Identification of Novel Rodent-Borne Orthohantaviruses in an Endemic Area of Chronic Kidney Disease of Unknown Etiology (CKDu) in Sri Lanka - Devinda S. Muthusinghe; Kenta Shimizu; Sithumini M. W. Lokupathirage; Zhouoxing Wei; Yomani D. Sarathkumara; G. R. Amanda Fonseka; Pavani Senarathne; Nobuo Koizumi; Tomonori Kawakami; Akio Koizumi; Chaminda Wickramasinghe; Hideki Ebihara; et al. (Viruses, 2021)
We reported the genetic evidence of circulating hantaviruses from small mammals captured in a chronic kidney disease of unknown etiology (CKDu) hotspot area of Sri Lanka. The high seroprevalence of anti-hantavirus antibodies against Thailand orthohantavirus (THAIV) has been reported among CKDu patients and rodents in Sri Lankan CKDu hotspots. We captured 116 small mammals from CKDu endemic regions in the Polonnaruwa District of Sri Lanka. Seven animals (five out of 11 Mus booduga and two out of 99 Rattus rattus) were PCR-positive for the hantavirus. A rat-borne sequence was grouped with a THAIV-like Anjozorobe virus. In contrast, Mus-borne sequences belonged to the THAIV lineage, suggesting a novel orthohantavirus species according to the phylogenetic analyses and whole-genome comparisons. Our genetic evidence indicates the presence of two THAIV-related viruses circulating in this CKDu endemic area, suggesting a basis for further investigations to identify the infectious virus in patients with CKDu and the CKDu induction mechanism of these viruses.